1995
DOI: 10.2175/106143095x133130
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic pretreatment of hazardous waste leachates in publicly owned treatment works

Abstract: Feasibility studies have been completed for an anaerobic pretreatment system designed to treat hazardous waste leachates in publicly owned treatment works. The system was designed to mitigate many of the problems associated with conventional aerobic treatment of these wastes and other types of dilute waterborne hazardous wastes. In this new approach, a contact/sorption stage consisting of an expanded bed of granular activated carbon (GAC) with an attached anaerobic biomass was used as a pretreatment device aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Because of the low TSS concentration and because of the presence of VOCs in the wastewater, anaerobic biofilters with granulated activated carbon (GAC) and with tezontle (volcanic porous stone widely available in Mexico) were also tested (Nacheva et al, 2003). GAC-reactors showed high effectiveness and stability, in concordance with the reported advantages of using GAC as biofilm attachment media for treatment of toxic or inhibitory wastewater (Suidan et al, 1993;Kupferle et al, 1995;Monteleb et al, 2001). The tezontle was also shown to be a good packed bed media, but process effectiveness and stability were lower.…”
Section: Introductionsupporting
confidence: 76%
“…Because of the low TSS concentration and because of the presence of VOCs in the wastewater, anaerobic biofilters with granulated activated carbon (GAC) and with tezontle (volcanic porous stone widely available in Mexico) were also tested (Nacheva et al, 2003). GAC-reactors showed high effectiveness and stability, in concordance with the reported advantages of using GAC as biofilm attachment media for treatment of toxic or inhibitory wastewater (Suidan et al, 1993;Kupferle et al, 1995;Monteleb et al, 2001). The tezontle was also shown to be a good packed bed media, but process effectiveness and stability were lower.…”
Section: Introductionsupporting
confidence: 76%
“…Results indicated that the two-stage system may be an effective 2,4-DNT treatment method. Kupferle et. al.…”
Section: Sorption Of Organicsmentioning
confidence: 99%
“…Many materials can be used as attachment media for the microbial population in the packed bed reactors and their characteristics are important for successful performance and operation. There are reports in the literature concerning the successful use of granular activated carbon (GAC) in fluidized bed anaerobic reactors to remove catechols (Suidan et al, 1980), polycyclic compounds (Wang et al, 1984) and phenols (Wang et al, 1986), in the treatment of wastes from the gasification of carbon (Suidan et al, 1983;Fox et al, 1988) and from leachates (Suidan et al, 1993;Kupferle et al, 1995). The presence of xenobiotic compounds in the chemical-pharmaceutical effluents justifies the use of GAC in the anaerobic packed bed reactors as well.…”
Section: Introductionmentioning
confidence: 99%